Sosialisasi parenting qur’ani sebagai pilar membangun generasi beriman dan berakhlak mulia di taman pendidikan al-qur’an nurul muttaqien desa plaosan wonosari kabupaten malang - Rivana, Rezza (Maliki Interdisciplinary Journal, 2025)
This community service activity aimed to enhance the understanding of both students and guardians at TPQ Nurul Muttaqien regarding the concept of Qur’anic parenting as a foundation for building a generation of faithful and virtuous individuals. Through this socialization, it is hoped that the guardians can implement parenting styles that align with the values of the Quran, namely parenting based on love, exemplary behavior, and effective communication. This socialization activity was conducted at TPQ Nurul Muttaqien, Dusun Plaosan, Desa Plaosan, Kecamatan Wonosari, Kabupaten Malang. The method used in this parenting socialization was the provision of materials. The socialization has successfully increased the understanding of the guardians about the importance of being role models for their children. They realize that Quranic parenting emphasizes the importance of love, discipline, and obedience. By applying these values in their daily lives, it is hoped that the guardians can guide their children to grow into individuals who are faithful and have noble character.